Bridging gaps in demographic analysis with phylogenetic imputation. Issue 4 (21st January 2021) - James, Tamora D.; Salguero‐Gómez, Roberto; Jones, Owen R.; Childs, Dylan Z.; Beckerman, Andrew P.
Abstract: Phylogenetically informed imputation methods have rarely been applied to estimate missing values in demographic data but may be a powerful tool for reconstructing vital rates of survival, maturation, and fecundity for species of conservation concern. Imputed vital rates could be used to parameterize demographic models to explore how populations respond when vital rates are perturbed. We used standardized vital rate estimates for 50 bird species to assess the use of phylogenetic imputation to fill gaps in demographic data. We calculated imputation accuracy for vital rates of focal species excluded from the data set either singly or in combination and with and without phylogeny, body mass, and life‐history trait data. We used imputed vital rates to calculate demographic metrics, including generation time, to validate the use of imputation in demographic analyses. Covariance among vital rates and other trait data provided a strong basis to guide imputation of missing vital rates in birds, even in the absence of phylogenetic information. Mean NRMSE for null and phylogenetic models differed by <0.01 except when no vital rates were available or for vital rates with high phylogenetic signal (Pagel's λ > 0.8). In these cases, including body mass and life‐history trait data compensated for lack of phylogenetic information: mean normalized root mean square error (NRMSE) for null and phylogenetic models differed by <0.01 for adult survival and <0.04 for maturation rate. Estimates of demographic metrics were sensitive to the accuracy of imputed vital rates. For example, mean error in generation time doubled in response to inaccurate estimates of maturation time. Accurate demographic data and metrics, such as generation time, are needed to inform conservation planning processes, for example through International Union for Conservation of Nature Red List assessments and population viability analysis. Imputed vital rates could be useful in this context but, as for any estimated model parameters, awareness of the sensitivities of demographic model outputs to the imputed vital rates is essential. Abstract : Cerrando Brechas en los Análisis Demográficos con Imputación Filogenética Resumen: Los métodos de imputación guiados filogenéticamente se han aplicado con poca frecuencia para estimar los valores faltantes en los datos demográficos, aunque pueden ser una herramienta poderosa para la reconstrucción de tasas vitales de supervivencia, maduración y fecundidad de especies de importancia para la conservación. Las tasas vitales imputadas podrían usarse para generar parámetros en los modelos demográficos para explorar cómo responden las poblaciones cuando se perturban las tasas vitales. Utilizamos estimaciones de tasas vitales estandarizadas para 50 especies de aves para analizar el uso de la imputación filogenética para llenar los vacíos en los datos demográficos. Calculamos la certeza de imputación para las tasas vitales de las especies focales excluidas del conjunto de datos por sí solas o en combinación y con y sin datos de filogenia, masa corporal y características de historia de vida. Usamos las tasas vitales imputadas para calcular las medidas demográficas, incluyendo el tiempo de generación, y así validar el uso de la imputación en los análisis demográficos. La covarianza entre las tasas vitales y otros datos de características proporcionó una base sólida para orientar la imputación de tasas vitales faltantes en las aves, incluso la ausencia de información filogenética. El NRMSE medio para los modelos nulo y filogenético difirió por <0.01 salvo cuando no hubo tasas vitales disponibles o para tasas vitales con una señal filogenética alta ( λ de Pagel > 0.8). En estos casos, la inclusión de la masa corporal y las características de historia de vida compensó la falta de información filogenética: el error cuadrático medio de la raíz normalizada media (NRMSE) para los modelos nulo y filogenéticos difirió por <0.01 para la supervivencia adulta y <0.04 para la tasa de maduración. Las estimaciones de las medidas demográficas fueron sensibles a la certeza de las tasas vitales imputadas. Por ejemplo, el error medio en el tiempo generacional se duplicó en respuesta a las estimaciones imprecisas del tiempo de maduración. Las medidas y datos demográficos certeros, como el tiempo generacional, son necesarios para orientar los procesos de planeación de la conservación; por ejemplo, a través de las valoraciones de la Lista Roja de la Unión Internacional para la Conservación de la Naturaleza y los análisis de viabilidad poblacional. Las tasas vitales imputadas podrían ser útiles en este contexto, pero como para cualquier tipo de parámetro de modelo estimado, el conocimiento de las sensibilidades del rendimiento del modelo demográfico es esencial para las tasas vitales imputadas. 摘要: 基于系统发育信息的插补模型很少用于估计种群统计数据中的缺失值, 但这种方法可能是重建受保护物种生存率、性成熟和繁殖力等生命统计数据的有力工具。估算的数据可以用于获得种群模型参数, 以探索当生命统计指标受到扰动时种群的响应。本研究使用五十种鸟类的标准化生命统计估计值, 评估了系统发育插补法在填补种群统计数据空缺中的应用。我们对排除在数据集之外的关注物种计算了插补准确率, 其中包括单独或联合计算, 纳入或不纳入系统发育、体重和生活史特征数据。接下来, 我们使用插补的生命统计数据计算了种群统计指标, 包括世代时长, 以验证数据插补在种群统计分析中的作用。结果显示, 生命统计指标和其它性状数据之间的协方差为估算鸟类缺失的生命统计数据提供了有力的依据, 即使在缺乏系统发育信息的情况下也是如此。除了无可用生命统计数据或有高系统发育信号的生命统计数据 (Pagel's λ > 0.8) 的情况之外, 无系统发育模型和系统发育模型的平均标准均方根误差相差小于 0.01 。在这些情况下, 纳入体重和生活史特征数据可以弥补系统发育信息的不足:成鸟存活率的无系统发育模型和系统发育模型的平均标准均方根误差相差不到 0.01, 而成熟率的相差小于 0.04 。种群统计指标的估计对插补获得的生命统计数据准确性很敏感。例如, 对性成熟时间估计不准确会导致世代时长估计的平均误差增加一倍。准确的种群统计数据和指标 (如世代时长) 可以为保护规划提供信息, 例如通过《国际自然保护联盟红色名录》评估和种群生存力分析。插补得到的生命统计数据在这方面可以发挥作用, 但是对于任何估算的模型参数都要认识到种群模型输出对生命统计数据插补的敏感性。【翻译: 胡怡思; 审校: 聂永刚】 用系统发育插补模型填补种群统计分析的空缺